2019
DOI: 10.3390/ma12233922
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength and Failure Pattern of Orthodontic Tubes Adhered to a Zirconia Surface Submitted to Different Modes of Application of a Ceramic Primer

Abstract: The aim of this study was to evaluate the shear bond strength of orthodontic tubes adhered to ceramics with the Transbond™ XT bonding resin (3M, Maplewood, MN, USA) while varying the surface treatment. Then, the adhesive remaining index (ARI) was verified, and the representative fracture patterns were evaluated via scanning electron microscopy. Forty-eight zirconia blocks were divided into three groups, varying the number of layers of the 10-methacryloyloxy-decyl dihydrogen phosphate (MDP) primer: one, two, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Based on the results, it was found that one application and two applications of phosphate-containing primer prior to the adhesive agent performed better than adhesive alone. This could be because 10-MDP, a phosphate monomer, was chemically bonded to the outermost surface of zirconia [ 25 ]. A phosphate group at one end of 10-MDP can be chemically bonded to the zirconia’s oxide layer and a double-bonded methacrylate, at the other end, can polymerize with resin composite/cement, resulting in increased bond strength [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, it was found that one application and two applications of phosphate-containing primer prior to the adhesive agent performed better than adhesive alone. This could be because 10-MDP, a phosphate monomer, was chemically bonded to the outermost surface of zirconia [ 25 ]. A phosphate group at one end of 10-MDP can be chemically bonded to the zirconia’s oxide layer and a double-bonded methacrylate, at the other end, can polymerize with resin composite/cement, resulting in increased bond strength [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…When working on CAD/CAM lithium disilicate, hydrofluoric acid followed by silane shows acceptable SBS values indifferent of adhesive, but slightly higher on roughened surface 56 or MDP adhesive. 57 On feldspathic, leucite based and lithium disilicate samples, testing showed lowest SBS when sandblasting only, feldspathic and lithium disilicate highest SBS with silica coating, leucite based ceramics showed highest SBS values for HF without silane, similar to silica coating. 58 Contradicting these findings, only one study shows that on both feldspathic and lithium disilicate ceramics, lowest SBS was achieved with HF, at a statistically significant difference and highest SBS was achieved when using diamond burs.…”
mentioning
confidence: 90%
“…1994 [47] Feldspathic Ceramic Silane/ no silane Sgn difference when silane was used 1999 [40] Amalgam SBS of the silane groups were higher and their microleakage percentages lower than those of the non-pretreated groups [51] IPS e-max CAD Ceramic Polycrystalline with MDP onlylowest values. [57] IPS E-max and zirconia Metallic E-max HF + MDP primer 1 coat; Zirconia MDP 1/2/3 coats Thermocycling E.max and zirconia with 3 MDP primer applications highest SBS [64] Lithium…”
Section: Non-feldspathic Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no gold standard or clinical recommendation exists for conditioning monolithic zirconia restorations when temporary brackets or attachments need to be bonded as part of fixed orthodontic treatment. Although different pretreatment methods have been investigated, most studies focus on the pretreatment methods and include only one attachment material 13 16 . Different attachment materials might also have an influence on the bonding strength between bracket and zirconia surface.…”
Section: Introductionmentioning
confidence: 99%